Unravelling the Secrets of Age Estimation: A Look at the Science Behind the Bone Analysis - Roopam Mourya; Ramkrishna Mishra; Surendra Kumar Pandey; Devashish Verma (Indian Journal of Forensic Medicine and Pathology, 2025)
Determining the age of unidenti𿿿ed human skeletalremains is one of the objectivesof forensic identi𿿿cation. Age is estimated using the articular surface of the ilium, pubic symphysis, acetabulum, clavicle, skull, and sternum. In November 2020, the body of an unknown 35-year-old man was found in a black plastic bag and transported to the Varanasi postmortem house for examination. Age can be inferred from changes in bone morphology as people age. The age had been estimated by the police. Bone morphology is the most accurate indicator of age, especially in a medicolegal setting. The deceased’s age is determined to be between 40 and 45 years old after a postmortem. For this middle age group estimation of age, most reliable morphological changes occur in acetabulum, pubic symphysis and the 4th rib.